Nomenclatural Notes on Two Species of Rotala L. (Lythraceae) from the Indian Region - Panigrahi, Sarojini (Indian Forester, 1976)
Rotala hexandra Koehne is the correct name for R. stipulata Blatt. and hallb., the latter being a superfluous name for the former and therefore, nomen. illegit. The combination R. indica (Willd.) Blatt. and Hallb. is also superfluous, being preceded by R. indica (Willd.) Koehne.